2020
DOI: 10.1515/hmbci-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the candidate microRNAs in thyroid fine-needle aspiration biopsy (FNAB) samples

Abstract: BackgroundThyroid cancer (TC) is known to be the most common endocrine malignancy with an incidence rate which has increased by 2.3-fold over the past 30 years. Approximately, 30% of the thyroid fine-needle aspiration biopsy (FNAB) outcomes are indecisive. Moreover, researchers recognized multiple differentially expressed microRNAs (miRNAs) as candidate diagnostic markers for thyroid nodules. The purpose of this study was to identify thyroid tumor-associated miRNAs in FNAB with the capacity to be developed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study was conducted on 174 samples obtained during FNABs from 168 patients. Another study showed that miR-181b, in combination with miR-146b, might be useful in differentiating between benign thyroid lesions and PTC lesions [ 59 ]. In a study performed on 20 malignant lesion samples and 20 samples containing benign lesions, Chen et al showed that miR-146b could be a useful PTC-screening biomarker [ 60 ].…”
Section: The Role Of Mirnas In Fine-needle Aspiration Biopsiesmentioning
confidence: 99%
“…The study was conducted on 174 samples obtained during FNABs from 168 patients. Another study showed that miR-181b, in combination with miR-146b, might be useful in differentiating between benign thyroid lesions and PTC lesions [ 59 ]. In a study performed on 20 malignant lesion samples and 20 samples containing benign lesions, Chen et al showed that miR-146b could be a useful PTC-screening biomarker [ 60 ].…”
Section: The Role Of Mirnas In Fine-needle Aspiration Biopsiesmentioning
confidence: 99%